Evaluation of the setup accuracy of a stereotactic radiotherapy head immobilization mask system using kV on‐board imaging - Ali, Imad; Tubbs, Jesse; Hibbitts, Kerry; Algan, Ozer; Thompson, Spencer; Herman, Terence; Ahmad, Salahuddin (Journal of applied clinical medical physics, 2010)
The purpose of this study was to evaluate setup accuracy and quantify random and systematic errors of the BrainLAB stereotactic immobilization mask and localization system using kV on‐board imaging. Nine patients were simulated and set up with the BrainLAB stereotactic head immobilization mask and localizer to be treated for brain lesions using single and hypofractions. Orthogonal pairs of projections were acquired using a kV on‐board imager mounted on a Varian Trilogy machine. The kV projections were then registered with digitally‐reconstructed radiographs (DRR) obtained from treatment planning. Shifts between the kV images and reference DRRs were calculated in the different directions: anterior‐posterior (A‐P), medial‐lateral (R‐L) and superior‐inferior (S‐I). If the shifts were larger than 2 mm in any direction, the patient was reset within the immobilization mask until satisfying setup accuracy based on image guidance has been achieved. Shifts as large as 4.5 mm, 5.0 mm, 8.0 mm in the A‐P, R‐L and S‐I directions, respectively, were measured from image registration of kV projections and DRRs. These shifts represent offsets between the treatment and simulation setup using immobilization mask. The mean offsets of 0.1 mm, 0.7 mm, and −1.6 mm represent systematic errors of the BrainLAB localizer in the A‐P, R‐L and S‐I directions, respectively. The mean of the radial shifts is about 1.7 mm. The standard deviations of the shifts were 2.2 mm, 2.0 mm, and 2.6 mm in A‐P, R‐L and S‐I directions, respectively, which represent random patient setup errors with the BrainLAB mask. The BrainLAB mask provides a noninvasive, practical and flexible immobilization system that keeps the patients in place during treatment. Relying on this system for patient setup might be associated with significant setup errors. Image guidance with the kV on‐board imager provides an independent verification technique to ensure accuracy of patient setup. Since the patient may relax or move during treatment, uncontrolled and undetected setup errors may be produced with patients that are not well‐immobilized. Therefore, the combination of stereotactic immobilization and image guidance achieves more controlled and accurate patient setup within 2 mm in A‐P, R‐L and S‐I directions. PACS numbers: 87.56.‐v, 87.56.Da